EDUCATION ON INITIAL HANDLING OF RESPIRATORY SYNCYTIAL VIRUS INFECTION IN MOTHERS OF KRAPYAK VILLAGE, TAHUNAN, JEPARA - Anisah Nurussyifa; Eko Retnowati; Ulviani Yulia Husna (LPPM Univ. Ibn Khaldun Bogor, 2026)
Respiratory Syncytial Virus (RSV) is one of the main causes of lower respiratory tract infections in children under five years old. Limited public knowledge regarding transmission, prevention, and early management of RSV increases the risk of severe complications, especially in rural areas such as Krapyak Village. This community service activity aimed to improve mothers’ knowledge regarding the early management of RSV infection through a health education program. The activity used a pre-experimental one-group pre-test post-test design involving 53 mothers with toddlers at Posyandu Mawar 6, Krapyak Village. The intervention included health education sessions, animated videos, interactive discussions, and leaflet distribution. Data were collected using a validated questionnaire and analyzed using the Wilcoxon signed-ranks test and N-Gain score. The results showed a significant increase in respondents’ knowledge after the intervention, with most participants achieving a good level of knowledge and an average N-Gain score in the moderate category. The program was effective in improving mothers’ understanding of early RSV management and is expected to support better preventive practices among toddlers in Krapyak Village.